A study on repeated fractures of highway construction (Concentration on MRR2 Highway) / Noor Irzaidah Kamarudin - Kamarudin, Noor Irzaidah (Faculty of Business and Management, 2010)
The purpose of this study is to know the reasons or causes behind the repeated pillar fractures on MRR2. Is it cracked because "hungry man's head" or because construction did not follow the standards. The Public Works Department (PWD) is the organization that responsible towards this issue. The disagreement between the Works Minister and PWD seem to stem from the question of which report to follow. After facing several disputes, the government of Malaysia then appointed British Halcrow Consultancy Ltd on 12 August, 2004 to study the cracks that have appeared on 31 of the32 crossbeams since 2000. Halcrow has found a rare phenomenon--the expansion of a chemical compound, ettringite, had caused serious cracks. The main cause of excessive cracking in the crosshead to the T-shaped pier is a deficiency in the design and the anchorage of the columns reinforced into the crosshead. There is also a deficiency in the design of the transverse reinforcement in the top of the crossheads to resist splitting forces between bearings.